Evaluating the Storage Behavior of Superior Low-Cost Anode Material from Biomass for High-Rate Sodium-Ion Batteries. Issue 7 (1st January 2017) - Zou, Guoqiang; Huang, Zhaodong; Zhao, Ganggang; Li, Simin; Hou, Hongshuai; Qiu, Xiaoqing; Ji, Xiaobo
Abstract : The superior low-cost porous carbon (SLPC) with an expanded interlayer spacing of 0.39 nm and a high surface area of ∼685 m 2 g −1 was obtained by a direct pyrolysis of dried camphor wood without additional activation. Benefiting from the expanded interlayer spacing and high surface area, the obtained carbon exhibited an excellent electrochemical sodium ion storage performance with a high reversible capacity of ∼310 mAh g −1 after 100 cycles between 3.0 and 0.01 V (vs Na + /Na) at a constant current density of ∼0.1 A g −1 . More importantly, an excellent rate capability of ∼120.6 mAh g −1 after 5000 cycles was delivered at a rather high current density of 5 A g −1, which is almost the best among the biomass-derived carbon anodes. The excellent performance of SLPC for SIBs may be attributed to the fast capacitance behavior and rapid mass transfer process profiting from porous structure of the carbon existing in biological tissue. Considering the superior low cost and excellent electrochemical sodium storage performance of SLPC, the SLPC might be a highly promising anode material for the practical application of SIBs.